The Duration of Reading the Qur'an with the Stress Levels in Medical Faculty Students in Palembang - Ghiffari, Ahmad; Muhammad, Syahrul; Ababil, M. Avif (Universitas Muhammadiyah Yogyakarta, 2021)
The level of stress in each education programs differ between medical students and other scholars. Students should able to cope to normalize their stress. The study aims to determine the relationship between the duration of reading the Qur'an with the level of stress on students. The study design was a cross-sectional study, with a simple random sampling. The collecting data technique was using the Depression Anxiety Stress Scale (DASS) questionnaires and duration questionnaires followed by the chi-square analysis. The respondents are 90 medical students of Universitas Muhammadiyah Palembang. The results showed that the duration of reading the Qur'an among students is poor, and the moderate duration is correlated with a good stress level (p=0,002). Concluded that there is a relation to the duration of reading The Qur'an with the level of stress in medical students.